Identification of candidate genes for soybean seed coat-related traits using QTL mapping and GWAS - Yang, Yue; Zhao, Tiantian; Wang, Fengmin; Liu, Luping; Liu, Bingqiang; Zhang, Kai; Qin, Jun; Yang, Chunyan; Qiao, Yake (Frontiers in Plant Science, 2023)
Seed coat color is a typical morphological trait that can be used to reveal the evolution of soybean. The study of seed coat color-related traits in soybeans is of great significance for both evolutionary theory and breeding practices. In this study, 180 F10 recombinant inbred lines (RILs) derived from the cross between the yellow-seed coat cultivar Jidou12 (ZDD23040, JD12) and the wild black-seed coat accession Y9 (ZYD02739) were used as materials. Three methods, single-marker analysis (SMA), interval mapping (IM), and inclusive composite interval mapping (ICIM), were used to identify quantitative trait loci (QTLs) controlling seed coat color and seed hilum color (SHC). Simultaneously, two genome-wide association study (GWAS) models, the generalized linear model (GLM) and mixed linear model (MLM), were used to jointly identify seed coat color and SHC QTLs in 250 natural populations. By integrating the results from QTL mapping and GWAS analysis, we identified two stable QTLs (qSC02 and qSC08) associated with seed coat color and one stable QTL (qHC08) related to SHC. By combining the results of linkage analysis and association analysis, two stable QTLs (qSC02, qSC08) for seed coat color and one stable QTL (qSHC08) for SHC were identified. Upon further investigation using Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, we validated the previous findings that two candidate genes (CHS3C and CHS4A) reside within the qSC08 region and identified a new QTL, qSC02. There were a total of 28 candidate genes in the interval, among which Glyma.02G024600, Glyma.02G024700, and Glyma.02G024800 were mapped to the glutathione metabolic pathway, which is related to the transport or accumulation of anthocyanin. We considered the three genes as potential candidate genes for soybean seed coat-related traits. The QTLs and candidate genes detected in this study provide a foundation for further understanding the genetic mechanisms underlying soybean seed coat color and SHC and are of significant value in marker-assisted breeding